Chemical properties of fleshy fruits in a rural-urban gradient: nutritional implications for urban frugivorous birds - Silva, Larissa Lais da; Costa, Sérgio Marques; Uliana, Maíra Rodrigues; Silva, Paulo Antonio (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
This study aims to analyze the chemical properties of fleshy fruits in urban and rural areas, investigating nutritional variations and possible impacts on frugivorous consumers, especially urban birds. Five plant species, common in urban and rural areas, were selected to assess the chemical properties of the fruits, including pH, soluble solids, acidity, sugars, vitamin C, pigments, phenols, and antioxidant capacity. Birds' consumption of fruits was also monitored in both environments. The originality of this study lies in the approach to the influence of urbanization on the chemical properties of fruits and their nutritional implications for urban frugivorous birds, contributing to the understanding of plant-animal interactions in urban contexts. The results indicated variations in the chemical parameters of the fruits among plant species and environmental gradients but without a clear pattern. Some species exhibited significant differences in their chemical compositions between urban and rural areas, suggesting adaptations to urban environmental stress. This study's theoretical and methodological contributions highlight the complexity of plant responses to urban environments and the importance of considering the specificities of each species and the environmental conditions to which they are exposed. This study's social and environmental implications are relevant for managing urban biodiversity and conserving frugivorous birds in cities, suggesting that the selection of plant species for urban afforestation should consider the fruits' nutritional properties and their attractiveness to local fauna.
Keywords: Urban ecology; Plant adaptation; Urban biodiversity